Bibliometric Analysis of Research on the CAGE Distance Framework in International Business - Judijanto, Loso (Eastasouth Institute, 2025)
This study investigates the research trends and intellectual structure surrounding the CAGE Distance Framework in international business through a bibliometric analysis. Using Scopus as the primary database and VOSviewer for visualization, the study examines patterns of publication, collaboration networks, and thematic developments over time. The findings indicate that research on the CAGE framework has evolved from general discussions of globalization and institutional distance to more refined applications in analyzing cultural, administrative, geographic, and economic differences. Keyword mapping reveals a concentration of studies on globalization, cultural distance, and administrative distance, with the “CAGE distance framework” emerging as a dominant conceptual anchor. The analysis also highlights the central contributions of leading scholars and institutions, as well as the growing integration of the framework into international management and strategy research. This study contributes by consolidating existing knowledge, identifying intellectual clusters, and outlining opportunities for future exploration, particularly in the context of digital globalization and sustainable business practices.